The immunological Warburg effect: Can a metabolic‐tumor‐stroma score (MeTS) guide cancer immunotherapy?. Issue 1 (10th March 2020) - Siska, Peter J.; Singer, Katrin; Evert, Katja; Renner, Kathrin; Kreutz, Marina
Abstract: The "glycolytic switch" also known as the "Warburg effect" is a key feature of tumor cells and leads to the accumulation of lactate and protons in the tumor environment. Intriguingly, non‐malignant lymphocytes or stromal cells such as tumor‐associated macrophages and cancer‐associated fibroblasts contribute to the lactate accumulation in the tumor environment, a phenomenon described as the "Reverse Warburg effect." Localized lactic acidosis has a strong immunosuppressive effect and mediates an immune escape of tumors. However, some tumors do not display the Warburg phenotype and either rely on respiration or appear as a mosaic of cells with different metabolic properties. Based on these findings and on the knowledge that T cell infiltration is predictive for patient outcome, we suggest a metabolic‐tumor‐stroma score to determine the likelihood of a successful anti‐tumor immune response: (a) a respiring tumor with high T cell infiltration ("hot"); (b) a reverse Warburg type with respiring tumor cells but glycolytic stromal cells; (c) a mixed type with glycolytic and respiring compartments; and (d) a glycolytic (Warburg) tumor with low T cell infiltration ("cold"). Here, we provide evidence that these types can be independent of the organ of origin, prognostically relevant and might help select the appropriate immunotherapy approach.